Effect of early detubularization on urethro-intestinal anastomosis during robot-assisted radical cystectomy and intracorporeal neobladder among bladder cancer patients - Ho Park, Jong; Lee, Hakmin; Lee, Sangchul; Hong, Sung Kyu; Byun, Seok-Soo; Oh, Jong Jin (Frontiers in Oncology, 2025)
PurposeUrethro-intestinal anastomosis (UIA) leak is a critical complication of robot-assisted radical cystectomy (RARC) with intracorporeal neobladder (ICN). Although early detubularization of ileal loop has been proposed to facilitate tension-free anastomosis, clinical evidence of its benefits in preventing UIA leaks is limited. We assessed its impact on UIA leak rates in bladder cancer patients undergoing RARC with ICN.MethodsWe retrospectively identified 580 patients who underwent radical cystectomy at Seoul National University Bundang Hospital between 2003-2025, of which 147 met inclusion criteria for RARC with ICN and were analyzed. We retrospectively reviewed 580 patients who underwent radical cystetomy at Seoul National University Bundang Hospital between 2003-2025. Patients were grouped by detubularization timing: before (early) or after (conventional) UIA. Baseline and perioperative features were compared. Univariable analysis and multinomial logistic regression identified potential predictors of UIA leaks and evaluated the independent effect of early detubularization.ResultsAmong 147 eligible patients, 93 underwent early and 54 underwent conventional detubularization. UIA leaks occurred in 6.1% (9/147), lower in the early group (2.2% vs. 13.0%, P = 0.031). Early detubularization (P = 0.031), length of hospital stay (P = 0.001), and prior abdominal surgery (P = 0.165) were potential predictors using a liberal selection threshold (P < 0.20). Multinomial regression identified early detubularization as an independent protective factor (OR, 0.154; 95% CI, 0.030–0.784; P = 0.024). Model goodness-of-fit was significant (χ² = 9.775, df = 4, P = 0.044; Nagelkerke R² = 0.096).ConclusionsEarly detubularization appears to reduce UIA leaks following RARC with ICN. Our findings support its adoption as a technical refinement to improve anastomotic outcomes, though further prospective validation is needed.